2018
DOI: 10.3390/molecules23061497
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, Chemical Stability, and In Vitro Cytotoxic Properties of Novel Quinoline-3-Carbaldehyde Hydrazones Bearing a 1,2,4-Triazole or Benzotriazole Moiety

Abstract: A small library of novel quinoline-3-carbaldehyde hydrazones (Series 1), acylhydrazones (Series 2), and arylsulfonylhydrazones (Series 3) bearing either a 1,2,4-triazole or benzotriazole ring at position 2 was prepared, characterized by elemental analyses and IR, NMR, and MS spectra, and then subjected to in vitro cytotoxicity studies on three human tumor cell lines: DAN-G, LCLC-103H, and SISO. In general, compounds 4, 6, and 8 substituted with a 1,2,4-triazole ring proved to be inactive, whereas the benzotria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 58 publications
3
26
1
Order By: Relevance
“…Furthermore, the activity of target compounds substituted at 1 and 3 positions on triazole ring is generally better than that of target compounds substituted at 2 position. The inhibitory activity of compounds of 1.1 and 1.3 were stronger than that of target compounds of 1.2 and 1.4 , suggesting that chloro‐substituent on pyridine ring is better than methoxyl group . On the other hand, the chlorine atom on the benzene ring appears to exert limited effects on the inhibitory activity with a chlrorine on the pyridine (comparing compound 1.1 to 2.1 , 1.3 to 2.3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the activity of target compounds substituted at 1 and 3 positions on triazole ring is generally better than that of target compounds substituted at 2 position. The inhibitory activity of compounds of 1.1 and 1.3 were stronger than that of target compounds of 1.2 and 1.4 , suggesting that chloro‐substituent on pyridine ring is better than methoxyl group . On the other hand, the chlorine atom on the benzene ring appears to exert limited effects on the inhibitory activity with a chlrorine on the pyridine (comparing compound 1.1 to 2.1 , 1.3 to 2.3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitory activity of compounds of 1.1 and 1.3 were stronger than that of target compounds of 1.2 and 1.4, suggesting that chlorosubstituent on pyridine ring is better than methoxyl group. [19] On the other hand, the chlorine atom on the benzene ring appears to exert limited effects on the inhibitory Figures 2 and 3). Overall, compound 2.5 showed the strongest inhibitory activities across four cell lines, which can be further optimized in future studies.…”
Section: Antiproliferative Activitymentioning
confidence: 99%
“…SAR indicated a benzotriazole analog at C-2 position enhances the anticancer activity as compared to triazole analog, emphasizing its further rationalization in the invention of lead potential anticancer agents (Scheme 25). [90] Synthesis of quinoline-hydrazides 128 a-l using quinoline hydrazine 126 and respective benzaldehydes 127 was reported by Subban Ravi et al The cytotoxicity was studied against the K562 cancer cell line, and compound 128 e was found to be most active with IC 50 = 26.93 μg/mL by MTT assay. Structure- activity relationship study suggested that compounds bearing electron-donating functionalities, particularly at the para position of aldehyde moiety, were found to be more active as compared to the electron-withdrawing groups.…”
Section: Quinoline-galactose Hybridsmentioning
confidence: 98%
“…It is recognized that chloroquine has a unique role as an antimalarial drug, and it has been successfully applied in clinical practice and is the first quinoline derivatives to be used in clinical practice. So far, the drug still has great application as an antimalaria [15–17]. After that, the design and synthesis of quinoline compounds have become one of the hot research directions in chemistry and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…However, 2‐position of quinoline drugs is easily oxidized after entering the body, which greatly reduces the efficacy of quinoline drugs [18–20]. Nevertheless, a large number of studies have been carried out to introduce functional groups on 2‐quinoline in order to ensure the efficacy of quinoline drugs [17–20]. Therefore, the introduction of amino groups at the 2‐position of quinoline in order to obtain a better efficacy of 2‐aminoquinoline drugs has attracted wide attention of chemists [21,22].…”
Section: Introductionmentioning
confidence: 99%